2015
DOI: 10.3389/fpsyg.2015.01613
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of individual psychological resilience in determining the professional quality of life of Australian nurses

Abstract: Research Topic: The aim of this study was to determine the relative contribution of trait negative affect and individual psychological resilience in explaining the professional quality of life of nurses.Materials and Methods: One thousand, seven hundred and forty-three Australian nurses from the public, private, and aged care sectors completed an online Qualtrics survey. The survey collected demographic data as well as measures of depression, anxiety and stress, trait negative affect, resilience, and professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
105
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 35 publications
17
105
2
6
Order By: Relevance
“…The result of the first hypothesis of this study aligns with those found in other studies (Cragie et al, ; Hegney et al, ; Hegney, Rees, Eley, Osseiran‐Moisson, & Francis, ). As predicted, the more resilient nurse shift workers were the more CS they had and the less resilient they were the more depression, anxiety, stress, STS, and burnout they had.…”
Section: Discussionsupporting
confidence: 92%
“…The result of the first hypothesis of this study aligns with those found in other studies (Cragie et al, ; Hegney et al, ; Hegney, Rees, Eley, Osseiran‐Moisson, & Francis, ). As predicted, the more resilient nurse shift workers were the more CS they had and the less resilient they were the more depression, anxiety, stress, STS, and burnout they had.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were reported in studies undertaken in other countries. Hegney, Rees, Eley, Osseiran‐Moisson, and Francis () reported that the mean score for resilience for Australian nurses was 70.02, somewhat lower than nurse leaders and community samples. Mealer et al.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study proposed that nurses with higher resilience reported higher job and compassion satisfaction (Hegney et al. ; Zheng et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience refers to an adaptive process when encountering with trauma, adversity, tragedy and stressors, which can be beneficial to personal strengths development, positive psychological adjustment and maintenance of good functional status (Campbell-Sills & Stein 2007). A previous study proposed that nurses with higher resilience reported higher job and compassion satisfaction (Hegney et al 2015;Zheng et al 2017). More resilient nurses reported less severe depressive state and burnout symptoms (Guo et al 2018;Hsieh et al 2016).…”
Section: Introductionmentioning
confidence: 99%